A Nona‐nuclear Heterometallic Pd3Pt6 "Donut"‐Shaped Cage: Molecular Recognition and Photocatalysis. Issue 28 (7th June 2018) - Preston, Dan; Sutton, Joshua J.; Gordon, Keith C.; Crowley, James D.
Abstract: We report a simple, low‐symmetry 2‐(1‐(pyridine‐4‐methyl)‐1 H ‐1, 2, 3‐triazol‐4‐yl)pyridine ligand that has both monodentate and bidentate binding sites. With platinum(II) and/or palladium(II) ions, two examples of a new nona‐nuclear metallo‐assembly have been accessed. These complexes were characterized by NMR spectroscopy, electrospray mass spectrometry (ESI‐MS), and in key cases, X‐ray crystallography. The cages possess three clefts comprised of planar cationic panels. This structural feature enables the binding of planar aromatic guests such as anthracene. More interestingly, the heterometallic assembly was able to catalyze the light‐induced [4+2] cycloaddition of anthracene with singlet oxygen. Abstract : A catalytic donut : A heterometallic (Pd II /Pt II ) nona‐nuclear metallo‐cage binds anthracene molecules and catalyzes their conversion into endoperoxides through singlet oxygen production in the presence of light.